Газотурбинная установка ГТЭ-190 - Субботин, В. Г.; Левченко, Е. В.; Швецов, В. Л.; Решитько, В. П.; Росинская, А. В. (Eastern-European Journal of Enterprise Technologies, 2009)
In the article there are presented the trends of the world electroenergetics development; it is justified the expedience of the development and arrangement of ГТЭ-190 gas-turbine manufacture at JSC ”Turboatom”. There are given the technical features and description of ГТЭ-190 design